2012
DOI: 10.1039/c1dt11358e
|View full text |Cite
|
Sign up to set email alerts
|

Heterometallic platinum(ii) compounds with β-aminoethylferrocenes: synthesis, electrochemical behaviour and anticancer activity

Abstract: A new family of heterometallic compounds 3-6 containing ferrocenyl and platinum(II) centers has been synthesized by reaction of 1-β-aminoethylferrocene (1) and 1,1'-bis(β-aminoethyl)ferrocene (2) with Pt(II) precursors. Using K(2)[PtCl(4)] as the Pt(II) source, the cis-square-planar neutral compounds [Fe{η(5)-C(5)H(4)(CH(2))(2)NH(2)}(2)PtCl(2)] (3) and [{Fe(η(5)-C(5)H(4)(CH(2))(2)NH(2))(η(5)-C(5)H(5))}(2)PtCl(2)] (5) were obtained. Reaction of cis-[PtCl(2)(dmso)(2)] with 1 and 2 resulted in the displacement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 74 publications
3
37
0
Order By: Relevance
“…The anticancer properties of certain molecules may be increased by the introduction of the organometallic ferrocene motif in the framework due to its low toxicity, high lipophilicity and unique electrochemical behavior. 27–29 Thus, several examples of heterometallic complexes incorporating ferrocene and a second cytotoxic metal (Au(I), 3036 Pt(II), 30,3742 Pd(II), 40,4345 Ru(II), 4650 Rh(I) 40,51,52 Ir(I), 40 and Cu(I) 53,54 ) appeared in the literature. In most cases the antiproliferative properties of the resulting compounds improved with respect of that of the corresponding ferrocene-based ligand, although synergistic effects of the effects of the two different metals were evaluated only in one case.…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer properties of certain molecules may be increased by the introduction of the organometallic ferrocene motif in the framework due to its low toxicity, high lipophilicity and unique electrochemical behavior. 27–29 Thus, several examples of heterometallic complexes incorporating ferrocene and a second cytotoxic metal (Au(I), 3036 Pt(II), 30,3742 Pd(II), 40,4345 Ru(II), 4650 Rh(I) 40,51,52 Ir(I), 40 and Cu(I) 53,54 ) appeared in the literature. In most cases the antiproliferative properties of the resulting compounds improved with respect of that of the corresponding ferrocene-based ligand, although synergistic effects of the effects of the two different metals were evaluated only in one case.…”
Section: Introductionmentioning
confidence: 99%
“…Complex 17 was completely inactive, but 18 was more potent than cisplatin against the resistant WiDr colon cancer cell line. Flow cytometry studies of 18 revealed that the trinuclear complex did not induce cell cycle arrest, but the cell cycle distribution was significantly different to that of cisplatin, thereby suggesting a different mode of action …”
Section: Platinummentioning
confidence: 98%
“…Cuadrado and colleagues investigated the combination of ferrocene and platinum by coordinating β‐aminoethylferrocenyl ligands to cisplatin fragments. This resulted in a cationic binuclear complex ( 17 ), a trinuclear complex ( 18 ) and a neutral binuclear complex ( 19 ).…”
Section: Platinummentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Besides platinum-based metallodrugs, transitionmetal-based complexes, such as ferrocene-bearing compounds, have shown strong antiproliferative effects in vitro as well as antitumor effects in vivo. [9,[11][12][13] Some of these compounds have shown promising IC 50 values ( Figure 3): (i) Nieto et al recently published the successful synthesis and first cell culture tests of a cis-configured ferrocene-platinum derivative, which showed in vitro activity in human breast, cervix, lung and colon cancer cells in the low micromolar range (partially exceeding the antiproliferative activity of cisplatin); [11] (ii) a trans-dichloridoplatinum(II) complex featuring two ferrocene-bound phosphane units was designed by Schulz et al, which yielded low IC 50 values in the micromolar range in the ovarian cancer cell line A2780. In 1996, Jaouen et al coupled ferrocene to 4-hydroxytamoxifen and modified the length of the carbon chain in order to optimize its pharmacological properties ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%